Comprehensive assessment of hydrogen production in argon‐water vapors plasmolysis. Issue 2 (30th December 2020) - El‐Shafie, Mostafa; Kambara, Shinji; Hayakawa, Yukio
Abstract: A simultaneous investigation of simulation and experimental analysis of hydrogen production from argon‐water vapor mixture as a function in DBD plasma applied voltage were studied. The H2 concentration results of two Ar‐H2 O simulation kinetics models were compared with the experimental results. The simulation analysis was implemented for Ar‐H2 O models with and without the dissociative attachment reaction (H − ). The effects of argon flow rate, input water vapor temperature, and water vapor flow rate on the H2 concentration from the Ar‐H2 O mixture were investigated. Furthermore, the effect of argon addition and reactor temperature on the hydrogen production from water vapor plasmolysis was performed. It was found that the hydrogen concentration was enhanced with the argon gas flow rate and plasma voltage increase. Moreover, the H2 concentration results of the water vapor simulation model selecting the dissociative attachment reaction (H − ) were nearly the same as that obtained from the experimental results. Also, it was observed that the energy efficiency was enhanced with the plasma input power increased. Moreover, the comparison showed that the hydrogen concentration of argon gas addition was lower than that obtained from water vapor plasmolysis at PTR heating temperature of 90°C. Abstract : The effects of argon flow rate, input water vapor temperature, and water vapor flow rate on the H2 concentration from the Ar–H2 O mixture were investigated. It was found that the hydrogen concentration from Ar–H2 O increases with increasing argon flow rate and plasma voltage.